EDUCATIONAL STRATEGIES FOR STRENGTHENING STUDENTS’ MORAL VALUES IN SCHOOLS - Yusrina Gultom; Anhar (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2024)
This study aims to explore the role of education in strengthening students’ character and moral development in schools. Character education is an essential aspect of the learning process because it not only focuses on academic achievement but also on shaping students’ ethical awareness, social responsibility, and positive behavior. In the modern era, students face various moral challenges influenced by technological development, social media, and changing social values. Therefore, education is expected to play a strategic role in guiding students to develop strong character and ethical behavior. This research employed a qualitative approach using a library research method. Data were collected from various sources, including books, academic journals, and relevant educational literature. The data were analyzed using content analysis to identify key themes related to character education, teacher roles, school environment, and family influence. The findings show that education has a significant role in shaping students’ character through the integration of moral values in learning activities. Teachers act as role models, while schools provide environments that support the practice of ethical behavior. Family support is also essential in strengthening value consistency in students’ daily lives. However, challenges such as limited curriculum time, lack of teacher training, and negative influences from technology still exist. The study concludes that character education requires collaboration between schools, teachers, parents, and society to effectively build students with strong moral values and responsible behavior.